2004
DOI: 10.1038/nbt971
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome characterization elucidates signaling networks that control human ES cell growth and differentiation

Abstract: Human embryonic stem (hES) cells hold promise for generating an unlimited supply of cells for replacement therapies. To characterize hES cells at the molecular level, we obtained 148,453 expressed sequence tags (ESTs) from undifferentiated hES cells and three differentiated derivative subpopulations. Over 32,000 different transcripts expressed in hES cells were identified, of which more than 16,000 do not match closely any gene in the UniGene public database. Queries to this EST database revealed 532 significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
255
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 316 publications
(275 citation statements)
references
References 45 publications
20
255
0
Order By: Relevance
“…Large-scale gene expression profiling of ES cells and somatic stem cells has revealed that TGF-β family signaling networks, especially Nodal signals, are likely to play important roles in the maintenance of the characteristics of ES cells [20]. Moreover, phosphorylation and nuclear localization of Smad2 induced by TGF-β, activin, or Nodal signaling were observed in undifferentiated human ES cells, and decreased upon early differentiation [21].…”
Section: Tgf-β Family Signaling In the Maintenance Of Pluripotency Anmentioning
confidence: 99%
“…Large-scale gene expression profiling of ES cells and somatic stem cells has revealed that TGF-β family signaling networks, especially Nodal signals, are likely to play important roles in the maintenance of the characteristics of ES cells [20]. Moreover, phosphorylation and nuclear localization of Smad2 induced by TGF-β, activin, or Nodal signaling were observed in undifferentiated human ES cells, and decreased upon early differentiation [21].…”
Section: Tgf-β Family Signaling In the Maintenance Of Pluripotency Anmentioning
confidence: 99%
“…3 Currently, much research is focused on differentiating hESCs towards clinically useful cell types, such as cardiomyoctyes 4 or dopaminergic neurons. 5 Whereas many of the genetic factors accompanying lineage development in hESCs are known, 6 the epigenetic changes remain poorly defined. Understanding how epigenetic regulation occurs in early human development could expedite our progress towards generating clinically useful cells.…”
Section: Introductionmentioning
confidence: 99%
“…ES cells and extraembryonic endoderm stem cells have been established from the inner cell mass (ICM), and trophoblast stem (TS) cells from the trophectoderm (5,6). Recently, major progress has been made in understanding the transcriptional regulatory circuitry that governs these early lineage decisions in the early mouse embryo and ES cells (7,8). Genetic studies in mice demonstrated that the transcription factors Oct4͞Pou5F1, Nanog, and Sox2 are crucial regulators of epiblast and ES cell identity (9)(10)(11)(12).…”
mentioning
confidence: 99%